Influence of processing conditions on the structure and properties of yttrium oxide ceramics - Baumer, V.N.; Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M.; Shekhovtsov, A.N.; Gordienko, L.S.; Yasukevich, A.S.; Kuleshov, N.V.; Gulevich, A.E.; Demesh, M.P. (Functional Materials, 2012)
By means of "wet" chemistry method Y₂O₃ nanopowder was obtained and characterized by X-ray diffraction analysis and differential thermal analysis. Transparent samples of Y₂O₃ and Y₂O₃:Nd ceramics were produced by vacuum sintering. Granulometric and phase compositions, crystal structure, spectral-kinetic and mechanical properties of the ceramics were studied.